Strategi Pembentukan Karakter Spiritualitas Keagamaan dan Cinta Tanah Air dalam Perspektif Filsafat Pendidikan Islam - Maragustam Maragustam (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
The current globalization is very influential towards forming one's character, whether to be a character or uncharacteristic. The issue is how to make someone character and uncharacteristic. From the matter, the researcher will answer, how is the strategy of the character formation of Homeland's religious spirituality and love? What are the values that need to be attributed? The scientific approach used was the philosophy of Islamic education with an eclectic incorporative. The study is entirely a kind of qualitative research-a library with various literature related to the character. Data collection with documentation. Its analytical techniques (1) Content analysis, (2) Miles and Huberman (data collection, data reduction, data display, and data verification), and (3) data triangulation. Research results; First, the strategy of establishing religious spirituality characters and the love of Homeland is habituation, moral knowing, moral feeling, immorality, and repentance with the throne, Takhalli, Tahalli, and Tajalli. Secondly, the primary value of implanted is religious-spiritual. This core value will give birth to Homeland's amount of love, integrity (honesty-trust), responsibility, respect, humility, tolerance, social care, love of science, hard work, patience, self-reliance, and social relationship.